Optimizing Islamic Education Learning Strategies in Cultivating Religious Culture Junior High School Students in the Independent Curriculum in Central Java - Ridho Riyadi; Ajrin Pradeni; Safarudin Yahya (Universitas Muhammadiyah Jember, 2026)
The implementation of the Independent Curriculum requires Islamic Religious Education (PAI) learning to focus not only on cognitive aspects but also on strengthening the character and religious culture of students in the school environment. However, at the practical level, Islamic Religious Education (PAI) learning still faces challenges, especially in the imagination of adaptive learning strategies based on student needs (contextual). The purpose of this study is to analyze the optimization of Islamic Religious Education (PAI) learning strategies in fostering religious culture in public junior high schools during the implementation of the Independent Curriculum in Central Java. The study used a qualitative paradigm with a case study design at Batang Public Junior High School. The data collected through observation, semi-structured interviews, and documentation. The research informants were the principal, Islamic Religious Education teachers, the curriculum vice-chair, the OSIS Spirituality Section, and students. Data analysis techniques used Miles Huberman and Saldana, which included data condensation, data display, and data verification. The results of the study indicate that optimization of Islamic Religious Education (PAI) learning in fostering students' religious culture is carried out through the implementation of differentiated learning in the classroom, the integration of religious project values to strengthen the Pancasila student profile (P5), and structured religious habits in the school environment. Supporting factors include teacher pedagogical competence and school policy support. Inhibiting factors include limited learning time and the complexity of curriculum administration. This study concludes that optimizing Islamic Religious Education (PAI) learning strategies plays a significant role in shaping students' religious culture in public junior high schools. Conceptually, this research strengthens the role of PAI as an instrument for shaping religious culture in public schools under the Merdeka curriculum. Practically, it provides recommendations for schools and teachers in developing contextual and sustainable PAI learning.